Law Enforcement Efforts for Illegal Electronic Cigarette Distribution without Excise Tax - Idham, Gilang Pradana (Estudiante Law Journal, 2025)
The purpose of this study is to find out how law enforcement efforts are made against the circulation of illegal electric cigarettes without excise. The research method used is empirical normative namely legal research regarding the enactment of normative legal provisions (codifications, laws or contracts) in action in every particular legal event that occurs in society. Especially on the performance of the Gorontalo customs officers in order to minimize the circulation of illegal e-liquid cigarettes without excise. The results of this study are the lack of supervision of the distribution of illegal e-cigarette tobacco excise products and the absence of direct supervision of sellers who are suspected of being the center of illegal liquid circulation, besides that customs need to socialize the circulation of excise-free e-cigarettes to the public in general either through mass media and other information media so that the public knows that this type of liquid is categorized as illegal goods which are prohibited from being distributed freely.